Global energy consumption and importance of renewable resources (Journal of Economic Research & Business Administration, 2017)
Energy is inevitable for human life and a secure and accessible supply of energy is crucial for thesustainability of modern societies. Achieving solutions to environmental problems that we face today requireslong-term potential actions for sustainable development. Economic growth, along with accompanyingstructural changes, strongly influences world energy consumption. As countries develop and livingstandards improve, energy demand grows rapidly. Increased demand for appliances and transportationequipment, and growing capacity to produce goods and services for both domestic and foreign markets,also lead to higher energy consumption. From this perspective, renewable energy resources are in alllikelihood the one of the most efficient and effective solutions. That is why there is an intimate connectionbetween renewable energy and sustainable development. This article presents current energy resourcesdata and human activity on it. As energy consumption and economic growth of world is directlydepends on each other, here the issue about efficiency of energy saving. Active and passive measureswhich can be taken by us, can solve some issues relating to energy consumption problems.